Research on interdisciplinary measurement and evolutionary path in the field of ophthalmology - Chunji, Lu; Yuwei, Liu; Fangyuan, Zhang; Zihan, Nie (Frontiers in Ophthalmology, 2025)
BackgroundInterdisciplinary collaboration is an inevitable trend in solving complex problems. As medical research deepens, the integration of theories, methods, and technologies from other disciplines with medicine has become an effective means to promote the development of medical research and address issues in the medical fieldObjectiveThere are significant differences in disciplinary intersections in different subfields of medicine, and this study, using ophthalmology as an example, aims to tap into the complex interrelationships between ophthalmology and other disciplines, to reveal interdisciplinary themes in ophthalmology, and to track the development and evolution of trans-ophthalmologic researchMethodsThis article takes ophthalmology as an example and uses the Rao-Stirling index to calculate the disciplinary distribution of journals cited in the literature of this field. By setting a threshold, it identifies interdisciplinary literature. Based on the LDA model, it conducts topic identification for the interdisciplinary literature to discover the interdisciplinary themes. Furthermore, it analyzes the evolution trends of these themes using the principle of similarity and visualizes the evolutionary paths.ResultsThe paper successfully linked 85,401 pieces of literature with WOS subject classifications, involving a total of 250 WOS subjects. The top 10 cited subjects are: Ophthalmology, Neurosciences, Surgery, Multidisciplinary Sciences, Biochemistry & Molecular Biology, Psychology, Medicine: Genetics & Heredity, Cell Biology, Genetics & Heredity, Clinical Neurology. A total of 18,573 pieces of literature with a Rao-Stirling index greater than 0.7 were selected as high interdisciplinary literature in Ophthalmology. The literature was divided into time slices of two years each, and scores for thematic coherence and thematic perplexity were calculated. Ultimately, twelve themes were identified for 2014-2015, eleven themes for 2016-2017, eleven themes for 2018-2019, ten themes for 2020-2021, and nine themes for 2022-2023. Based on the calculation of thematic similarity, three main evolutionary paths were summarized. The evolutionary paths are: “1-1, 1-2, 1-3, 1-5, 1-6, 1-9,1-10→2-1, 2-4, 2-7, 2-8, 2-9, 2-10→3-4, 3-8, 3-10→4-1, 4-5, 4-8, 4-10→5-5, 5-8, 5-9”, “1-1, 1-2, 1-3, 1-5, 1-6, 1-9,1-10→2-1, 2-4, 2-7, 2-8, 2-9, 2-10→3-4, 3-8, 3-10→4-1, 4-5, 4-8, 4-10→5-5, 5-8, 5-9”ConclusionsThis study conducts a comprehensive analysis of interdisciplinary themes in ophthalmology through the application of the Rao-Stirling index and the LDA model, revealing trends of multidisciplinary collaboration and evolving topics. To facilitate the integration of these themes, the research proposes several recommendations: first, to promote interdisciplinary collaboration in order to establish an innovative ecosystem that spans various fields; second, to develop a systematic funding framework for research and enhance the evaluation system for interdisciplinary projects; third, to implement reforms in ophthalmic education aimed at strengthening the cultivation of interdisciplinary talent; and fourth, to expand the scope of academic journal inclusions by establishing dedicated sections for interdisciplinary research.